Integrating biodiversity considerations into urban golf courses: managers' perceptions and woody plant diversity in the Eastern Cape, South Africa. Issue 4 (4th July 2017) - Jarrett, M.; Shackleton, C. M.
ABSTRACT: Rapid rates of urbanisation affect biodiversity through habitat fragmentation and loss. Because urban golf courses are large green spaces, they potentially harbour much biodiversity if managed for such. The area of untransformed land of golf courses in the Eastern Cape (South Africa) was determined using Geographic Information System (GIS), the woody plant composition of a subsample was determined by field sampling and the greenkeepers were interviewed. There was a significant relationship between climate and woody cover, species richness and percentage native plants but not species diversity. There was no relationship between management scores and species richness, diversity and percentage native. Significant relationships were evident between woody plant species richness and course income, number of grounds staff, number of club members and greenkeepers' years of experience. These results suggest a complex suite of factors that play a role in the woody plant composition of urban golf courses and their contribution to urban biodiversity.